The Effect of Training and the Implementation of Occupational Health and Safety Systems on Employee Productivity of PT. PP. London Sumatra Indonesia Tbk Branch Office Medan - Kelly Dwi Putri; Nora Anisa Br. Sinulingga (SEAN Institute, 2021)
The aim of this research was to determine the influence of training and occupational health and safety (OHS) to work productivity of employees at PT. PP. London Sumatra Indonesia Tbk Branch office Medan. Type of this research is a quantitative research that was analyzed with multiple linear regression with SPSS Statistics 22. The data source is primary and secondary collected by using some techniques: observation, interview, questionnaire, and documentation. The populations in this research is 115 person, while the samples amounted 54 correspondents which is obtained with the Slovin formula. The result of this research, based on partially and simultaneous test, proved that the training and occupational health and safety (OHS) have significant influence on work productivity of employees at PT. PP. London Sumatra Indonesia Tbk Branch Office Medan. Between the two, occupational health and safety (OHS) is the most dominant influence on work productivity of employees.